Biodiversity and Economic Growth: Stabilization Versus Preservation of the Ecological Dynamics - Simone Borghesi; Angelo Antoci; Paolo Russu (Fondazione Eni Enrico Mattei (FEEM), 2004)
This work examines the impact that economic growth can have on biodiversity and on the ecological dynamics that would naturally emerge in the absence of human activity. The loss of biodiversity may induce policy-makers to implement defensive actions that prevent single species from extinction. These defensive actions, however, may deeply alter the natural dynamics of interaction between species, leading to an ecological equilibrium that is completely different from the one that would exist in the absence of human intervention. This suggests that there might exist a conflict between preserving biodiversity (through stabilization of the ecological system) and preserving the intrinsic features of the ecological dynamics. To investigate this issue more deeply, we analyze the impact that different objective functions and defensive technologies can have on the natural ecological dynamics, and show that human action can modify the stability of the ecological fixed points. From the simple analytical formulations adopted in the paper, it emerges that it is possible to stabilize the ecological fixed point and consequently to avoid the extinction of a species, even in the absence of defensive expenditures specifically finalized at the protection of that species. The stabilizing. effect of human intervention, however, turns out to be enhanced when specific defensive expenditures are implemented. Finally, numerical simulations suggest that human activity can have an even deeper impact on the ecological dynamics, substantially modifying not only the stability of the fixed points, but also their number.
Keywords: C61; C62; Q20; 330; Biodiversity; Growth; Defensive actions; Ecological dynamics; Wirtschaftswachstum; Artenvielfalt; Umweltökonomik; Theorie